Forced Environmental Migration: Ethical Considerations for Emerging Migration Policy. Issue 1 (2nd January 2016) - Marshall, Nicole
Abstract: This paper gives a normative assessment of the problem of forced environmental migration, or, migration driven primarily by environmental events, drawing particular attention to the framing of citizen and non-citizen rights in the context of anthropogenic climate change. It explores a moral imperative to install special migration rights for Environmentally Displaced Peoples and briefly assesses the ability of current domestic migration policy to offer such rights. The paper concludes by offering three theoretical policy-oriented exercises, ultimately locating tiered citizenship as the most immediate ethically robust and politically acceptable solution to the challenge of environmental displacement.